Agricultural Productivity Across Prussia During the Industrial Revolution: A Thünen Perspective - Michael Kopsidis; Nikolaus Wolf (European Historical Economics Society (EHES), 2012)
This paper explores the pattern of agricultural productivity across 19th century Prussia to gain new insights on the causes of the 'Little Divergence' between European regions. We argue that access to urban demand was the dominant factor explaining the gradient of agricultural productivity as had been suggested much earlier theoretically by von Thünen (1826) and empirically by Engel (1867). This is in line with recent findings on a limited degree of interregional market integration in 19th century Prussia.
Keywords: N53; O43; O47; Q13; R12; 330; Prussia; Agricultural Productivity; Industrialisation; Market Access